Yontmataş buluntu toplulukları ışığında Ankara: neyi biliyoruz? Neyi bilmiyoruz? Yeni değerlendirmeler ve sonuçlar - Kartal, Metin (My University, 2005)
For no apparent reason, Central Anatolian Paleolithic Age studies have been neglected since the mid 20th century. And it seems that our knowledge is very poor about knapped stone findings in this region. The goal of this study is hopefully to provoke a debate among the Paleolithic Age archaeologists. Some of previous researchers such as Kansu, Kökten, Ozansoy, Pfannenstiel etc. mainly focused on Ankara’s knapped stone findings during the mid 20th century. We must also acknowledge Campbell-Thompson, Bittel, İnan and Pittard who had worked in this region in the first half of the 20th century prior to Kansu and his friends. What we mainly find in the papers of these researchers are impressive terms such as: “levalloiso-moustérien”, “aurignacien” and “tardenoasian”. But today, some questions that come to mind are “Are these the correct terms for Central Anatolia?”, “What were the shortcomings of earlier research?” and “What answers can we propose today?” First of all, we must consider not only the geographic position of Central Anatolia but also the possible cultural connections between the Balkans and the Levant and/or the Taurus-Zagros cultural zone. Some archaeologists whom we have consulted thought that Central Anatolia doesn’t play a role in the distribution of bifacial tools. Yet since it is obviously possible to see that the necessary evidence has already been obtained from Central Anatolia, today this hypothesis seems absolutely speculative. On the other hand, beside the existence of the bifacial tools which belong typologically to the lower Paleolithic period, there are also many findings from the middle Paleolithic period that reflect the moustérien type of assemblages with or without the levallois knapping strategies. Up to now, we have no basis for saying the aurignacien tradition is present in Central Anatolia. But this tradition is currently identified in the Karain B cave’s sequence in southwestern Anatolia in the new excavations. Although, it seems impossible to identify tardenoasian culture not only in Central Anatolia but also all around Anatolia on the basis of existing data. It is not surprising that we also have some findings of possible food production phases from Ankara. It is known that the Aşıklı, Çatalhöyük and Pınarbaşı sites represent the first food production phases in Central Anatolia. Of course we can not give absolute data about this period from these few findings. We must consider these findings as initial clues from Ankara and its surroundings. Consequently, in addition to the surface collections of knapped stone findings, Ankara and its surrounding territories need more in situ findspots to establish the cultural sequence and the dates of this cultural sequence’s sub-phases during the pleistocene and the beginning of the holocene.